Postreplication repair and PCNA modification in Schizosaccharomyces pombe. - Frampton, J; Irmisch, A; Green, C; Neiss, A; Trickey, M; Ulrich, H; Furuya, K; Watts, F; Carr, A; Lehmann, A (2006)
Ubiquitination of proliferating cell nuclear antigen (PCNA) plays a crucial role in regulating replication past DNA damage in eukaryotes, but the detailed mechanisms appear to vary in different organisms. We have examined the modification of PCNA in Schizosaccharomyces pombe. We find that, in response to UV irradiation, PCNA is mono- and poly-ubiquitinated in a manner similar to that in Saccharomyces cerevisiae. However in undamaged Schizosaccharomyces pombe cells, PCNA is ubiquitinated in S phase, whereas in S. cerevisiae it is sumoylated. Furthermore we find that, unlike in S. cerevisiae, mutants defective in ubiquitination of PCNA are also sensitive to ionizing radiation, and PCNA is ubiquitinated after exposure of cells to ionizing radiation, in a manner similar to the response to UV-irradiation. We show that PCNA modification and cell cycle checkpoints represent two independent signals in response to DNA damage. Finally, we unexpectedly find that PCNA is ubiquitinated in response to DNA damage when cells are arrested in G2.